Scientific selling : creating high-performance sales teams through applied psychology and testing - Martini, Nancy, 1959- (Wiley, 2012)
Sales managers have the most difficult job in the business world. They are responsible not just for revenue, but also for the hiring, coaching, training, and deployment of the employees who must generate it. Before the advancements that inspired Scientific Selling, sales managers had few tools to help them succeed at these disparate yet essential tasks. Today, however, the scientific approaches described in this book allow sales managers to more effectively measure, refine, and improve every aspect of the sales environment. Using easily-understood examples, graphics, charts, and explanations, Scientific Selling describes how to: predictably improve sales results; attract and retain top sales performers; sharply decrease employee turnover; spend sales training dollars more wisely; better target sales coaching efforts; move into consultative selling more quickly; and much more. Scientific Selling features over a dozen case studies illustrating exactly how scientific measurement and testing have improved sales performance within different kinds of sales groups inside multiple industries.